SOURCE IDENTIFICATION OF TRACE ELEMENTS IN PARTICULATE MATTER REFERENCE TO ENVIRONMENT OF QUETTA, PAKISTAN - Nida Kazmi; Manzoor Iqbal Khattak; Adnan Afridi; Munnaza Saeed; Hamidullah (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
The air quality in Balochistan's capital city of Quetta was the subject of a recent research. To do this, researchers analyzed trace element levels in PM10 and PM2.5 particles collected daily from a significant urban region. With a value of 1,998.0 ng m-3, PM2.5 had the highest levels of Zn in the surrounding environment. To determine the relative contributions of different sources of specific metal components in airborne particles, multivariate receptor modeling techniques such as principal component analysis and cluster analysis were used. Based on the data, it seems that fossil fuel combustion in stationary sources and vehicle traffic are the main culprits responsible for the trace metals found in Quetta's urban aerosols as the air quality is much worse in underdeveloped countries. Low air quality, which is a result of both ignorance and bad social and economic conditions, claims the lives of millions of people every year. Air pollution monitoring in Pakistan has been the subject of several studies, despite a lack of comprehensive research in the field. It is well-established that both pollutants have negative impacts on human health when exposed to them for an extended period of time, and several studies have proven the different negative health outcomes that may occur as a result of this study too.